The Effect of Learning Entrepreneurship Courses on the Interests of Students of the Economics Education Study Program for Entrepreneurship - Debora Nila Sari Hutasoit; Sotarduga Sihombing; Herlina Hotmadinar Sianipar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The problem in this research is the lack of student interest in entrepreneurship. The purpose of this study was to determine the Effect of Learning Entrepreneurship Courses on the Interests of Students of the Economics Education Study Program for Entrepreneurship. This research was conducted at the University of HKBP Nommensen Pematang Siantar. The population in this study were 82 students and all the populations became a simple of 82 students in total sampling. Data collection techniques using observation and questionnaires (questionnaire). The data analysis technique used to test the hypothesis is a simple regression analysis technique. Based on data analysis using Excel, the equation Y = 13.447 + 0.890 X. Furthermore, the learning variable for entrepreneurship courses (????) has a positive and significant influence between learning entrepreneurship courses on the interest of Economic Education Students for Entrepreneurship. This can be seen from the results of Simple Regression calculations (t test) in the entrepreneurship course (????) carried out using excel which shows the value of thitung > ttabel (9.008 > 1.664) and a significant value (0.001 <0.05)